Offenders convicted of child sexual exploitation material offences: characteristics of offenders and an exploration of judicial censure - Christensen, Larissa S. (Psychiatr Psychol Law, 2020)
Research on the discernments of child sexual exploitation material (CSEM), particularly delivered by judicial officers, is limited. Sentencing remarks can disseminate formal messages about the offender’s character while censuring crime. This study aimed to: obtain a deeper understanding on the characteristics of CSEM offenders and explore the censure sentencing judiciary impart. An exploratory content analysis conducted on sentencing remarks of 29 offenders across a 10-year period in Australia found all offenders were male, mostly middle-aged, with diverse employment and education. Most possessed and/or accessed CSEM involving: children under three and the most severe category (sadism/bestiality). Characteristics and censure involved: offender’s motivations and explanations for offending (sub-themes included poor mental health and substance abuse, downplay or denial, and addiction); CSEM offences are not victimless crimes; and disparities in the offender’s public versus private life. This study’s findings are valuable for law, psychology and social work disciplines across Australia and internationally.